Back Cover: Super‐Hydrated Zeolites: Pressure‐Induced Hydration in Natrolites (Chem. Eur. J. 33/2013). Issue 33 (2nd August 2013) - Seoung, Donghoon; Lee, Yongmoon; Kao, Chi‐Chang; Vogt, Thomas; Lee, Yongjae
<x xml:space="preserve">Abstract</x> Alkali‐metal‐exchanged natrolites (A16Al16Si24O80⋅n H2O; A=Li, K, Na, Rb, and Cs) in the presence of water undergo unprecedented increases in volume when subjected to pressure, a change that is caused by hydration of the framework (pressure‐induced hydration; PIH) and is inversely proportional to cation radius (NFC = non‐framework cations). For more details, see the Full Paper by Y. Lee et al. on page 10876 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>